Measuring liquid density in a system for ensuring uniformity of measurements - Bakovets, Nickolay V.; Konicheva, Ekaterina N. (Journal of the Belarusian State University. Physics, 2022)
The article presents the results of a study aimed at creating the national standard for liquid density. The standard provides reproduction, storage and transmission of the liquid density unit in the range from 650 to 2000 kg/m3. Based on the method of hydrostatic weighing, the measurement of liquid density was implemented in accordance with the GOST OIML R 111-1-2009 «State system for ensuring the uniformity of measurements. Weights of classes Е1, Е2, F1, F2, M1, M1–2, M2, M2–3 and M3. Part 1. Metrological and technical requirements». It is shown that the use of a high-precision mass comparator can significantly reduce the systematic measurement error and the standard deviation when reproducing and transferring the unit of liquid density to reference measuring instruments of the 1st and 2nd category and working measuring instruments. A method for transferring a unit of liquid density by means of a standard density measure – a silicon sphere and a comparator liquid – has been implemented, which made it possible to exclude the transfer link in the form of a standard liquid density solution. In the range of reproduction, storage and transmission of the liquid density unit, a systematic error of 2.1 ⋅ 10–3 kg/m3 was obtained, the standard deviation in the reproduction of the liquid density unit was 4.0 ⋅ 10–4 kg/m3, the standard deviation of the total error in the transmission of the liquid density unit 3.14 ⋅ 10–3 kg/m3.